If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-82=5(1-2x)-7
We move all terms to the left:
-82-(5(1-2x)-7)=0
We add all the numbers together, and all the variables
-(5(-2x+1)-7)-82=0
We calculate terms in parentheses: -(5(-2x+1)-7), so:We get rid of parentheses
5(-2x+1)-7
We multiply parentheses
-10x+5-7
We add all the numbers together, and all the variables
-10x-2
Back to the equation:
-(-10x-2)
10x+2-82=0
We add all the numbers together, and all the variables
10x-80=0
We move all terms containing x to the left, all other terms to the right
10x=80
x=80/10
x=8
| 30-14x=16-7x | | 4x=-98 | | 13=t1/5 | | 1608=8e+8 | | 21-6x=24+x | | 4z-2z(1+3)=32 | | -40=4(1+2x)+5(2+2x) | | 4907=7z+7 | | 4+y/2+y=46 | | 9(a-4)+3(2a+5)=7(3a-4)-6a+7 | | c^2=2c^2-12c+20 | | -35=5(3+4m)+3(2-2m) | | 18y-8y^2=8 | | 4x=2x=14 | | 5p+3-p=2p-4 | | 12x=20+2x | | 79=8m+7 | | 53+p=14.50 | | 17x1=3x+8 | | 3c^2-12c+20=0 | | 5(1+4x)-(5x-5)=25 | | 7x−2=3 | | ×2+3x-4=6 | | 12s-7=10 | | 3/4(12a+12)=45 | | 12s-7=15 | | -4(x+5)+2x=-20 | | 3(x-4)+2x=21 | | 12s-7=5 | | 57=3(4-3x) | | 9y+2=47 | | 2x+4=29x |